Matte-slag separation behavior during reduction process of iron phase - liu, yuxuan; Wei, yonggang; Zhou, Shiwei; li, bo; wang, hua (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The Isa smelting furnace discharges the matte and slag in the same tapping hole. As a result, an electric furnace needs to clean the slag. In the present study, the copper slag cleaning in an electric furnace, particularly the separation of the matte from the slag during the reduction process, was investigated. For Fe3O4 to FeO, the foaming slag in the melt disappeared and the matte particles settled discernibly. With the formation of the metallic iron, the viscosity of slag increased and the foaming slag formed again, hindering the sedimentation of the matte. The microstructure of the slag and the existence of the metallic iron found in the slag were analyzed in detail. The results obtained in this paper provide a theoretical basis for the reasonable control of the transformation of Fe3O4 during the copper slag cleaning in an electric furnace. Keywords: Cleaning; magnetite; reduction; foaming slag.